Dakwah di Tengah Masyarakat Plural: Analisis Konsep dan Pengalaman Historis Islam - Mastori, Mastori; Marsambas, Marsambas (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2023)
AbstractThis study discusses the relationship between ulama and umara and its implementation for the development of Islam, especially during the Islamic sultanate. The subjects of this research were two great Islamic figures who became role models for the relationship between ulama and umara, namely Sheikh Nuruddin Ar Raniry and Sunan Kalijaga. The main issue that is the focus of this research is the progress or role of ulama and umara' during the past Islamic empire. It is hoped that the positive values of the relationship between ulama and Umara in the past in this study can become a model model for the present. The research method used in this research is descriptive qualitative. The results of this study show that ulama and umara' in the history of the past Islamic sultanate system in the archipelago there was a very strong collaboration. The umara' policy cannot be separated from the results of the thoughts or ijtihad of the ulama' based on the Koran and Sunnah of the Prophet Muhammad SAW. In fact, it is not uncommon for ulama to also have the position of sultan/umara'.